Two Novel Rare Strongly Linked Missense SNPs (P27R and A85G) Within the GDF9 Gene Were Significantly Associated With Litter Size in Shaanbei White Cashmere (SBWC) Goats - Bi, Yi; Li, Jie; Wang, Xinyu; He, Libang; Lan, Kangshu; Qu, Lei; Lan, Xianyong; Song, Xiaoyue; Pan, Chuanying (Frontiers in Veterinary Science, 2020)
As a high-fertility candidate gene, growth differentiation factor 9 (GDF9) gene plays a crucial role in early folliculogenesis in female mammals. In our previous study, two strongly linked missense single nucleotide polymorphisms (SNPs), p.Glutamine320Proline (Q320P) and p.Valine397Isoleucine (V397I) SNPs loci and a 12-bp indel within goat GDF9 gene were found to have significant association with litter size. Furthermore, our group summarized all reported SNPs loci within GDF9 gene and the effect on litter size in more than 30 kinds of goat breeds and found almost all researches were focused on the single locus, neglecting combined effects of different loci, which played key roles in regulating litter size. To uncover more SNPs loci act as effective molecular markers, as well as combined effects of these SNPs loci, whole-genome sequencing was used to screen the possible SNPs loci in goat GDF9 gene. In this study, three SNPs loci, p.Proline27Alanine (P27R), p.Leucine61Leucine (L61L), and p.Alanine85Glycine (A85G), were identified. Among the three SNPs, two rare missense SNPs loci (P27R and A85G) were uncovered being strongly linked with each other (D’ value= 0.926, r2 value= 0.703). Both P27R and A85G loci had two genotypes: wild types and heterozygosity types. A85G exerted a significant effect on litter size (P= 0.029) in SBWC goats, and the heterozygosity genotype was superior in comparison with the wild type, which was consistent with P27R. No significant association was found in P27R. However, the diplotype of P27R and A85G was identified to have a superior effect on litter size (P= 3.8E-15). Hinted that these two SNPs influenced litter size of goats simultaneously. Combining our previous studies, we would like to consider GDF9 gene as the major high-fertility candidate gene and A85G locus as a promising SNP in affecting litter size of goats. Results above might close the gap in the research on rare mutations as well as provide crucial molecular markers which could apply to the marker-assisted selection (MAS) goat rearing in selecting superior individuals.